2015
DOI: 10.1039/c5cc00826c
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabenzanthanthrenes by mitigation of rearrangements in the planarization of ortho-phenylene hexamers

Abstract: In general, ortho-phenylene hexamers are not good substrates for oxidative planarization because of competing backbone rearrangements. However, by first planarizing the ends, a target tetrabenzanthanthrene has been obtained by oxidation in good yield. DFT calculations suggest that the larger polycyclic aromatic subunits of the preplanarized substrate increase the rate of planarization relative to that of rearrangement. By implication, it may be possible to prepare graphene structures that cannot be made direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
(41 reference statements)
0
9
0
1
Order By: Relevance
“…Another example of this trend has been presented by Hartley and co‐workers, who have shown that terphenyl 158 undergoes single oxidative coupling and a 1,2‐aryl shift to afford 160 and not hexacycle 159 (Scheme ) …”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 90%
See 1 more Smart Citation
“…Another example of this trend has been presented by Hartley and co‐workers, who have shown that terphenyl 158 undergoes single oxidative coupling and a 1,2‐aryl shift to afford 160 and not hexacycle 159 (Scheme ) …”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 90%
“…[152] Another example of this trend has been presented by Hartley and co-workers,w ho have shown that terphenyl 158 undergoes single oxidative coupling and a1 ,2-aryl shift to afford 160 and not hexacycle 159 (Scheme 23). [153] Under oxidative coupling conditions (FeCl 3 or DDQ), acenes bearing aryl groups attached to the central benzene rings generally cyclize to form new five-membered rings. [142,144] Scheme 24 depicts an especially interesting example,w here oxidation of symmetric tetracene 161 led to the unsymmetric product 162 containing two new rings of different sizes:five-and six-membered.…”
Section: Large Planar Pahs Expanded Acenes and Nanographenesmentioning
confidence: 99%
“…The clean, high-yielding formation of 3 without any optimization was quite surprising. It is well known that unwanted side reactions such as arene rearrangement (24) and aromatic chlorination often take place with polyaromatic compounds (23) in Scholl chemistry. For example, when polyphenylene 4, which can be prepared by the nickel-catalyzed reductive dimerization of 1a (25), was subjected to the standard Scholl conditions (FeCl 3 , CH 2 Cl 2 , 0°C), the fully fused product 3 was not obtained; instead, a complex mixture of various unidentified products (most likely arene rearrangement products) was obtained.…”
mentioning
confidence: 99%
“…Ein weiteres Beispiel für diesen Trend wurde von Hartley et al. vorgestellt, die gezeigt haben, dass das Terphenyl 158 eine einfache oxidative Kupplung und eine 1,2‐Arylverschiebung durchläuft, was zu 160 und nicht zum Hexacyclus 159 führt (Schema ) …”
Section: Intramolekulare Oxidative Aromatische Kupplungunclassified